2015
DOI: 10.2495/sdp-v10-n3-347-360
|View full text |Cite
|
Sign up to set email alerts
|

Domestic activities and pm generation: a contribution to the understanding of indoor sources of air pollution

Abstract: Few researches on domestic indoor air pollution have given quantitative information on the variation of the characteristics of the indoor source of particulate matter (PM). The purpose of this work was to investigate the emission characteristics of the common indoor particle sources.More specifically, this paper is intended to contribute to the understanding of how normal domestic activities could affect the human health. The emission sources of PM studied in this work was cooking, vacuuming, ironing and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Weschler 1 believes that increases in the last few decades of use of personal computers, electronic games and even television have had a big effect on the overall time people spend at home indoors. The latter is proven to be linked with negative effects on occupant health due to possible higher exposure to pollutants [2][3][4] but there is also a need to know how long occupants spend in different rooms to understand their potential levels of exposure to indoor pollutants. This is especially important for studies that model the spread and effect of indoor pollutants rather than measuring them.…”
Section: Introductionmentioning
confidence: 99%
“…Weschler 1 believes that increases in the last few decades of use of personal computers, electronic games and even television have had a big effect on the overall time people spend at home indoors. The latter is proven to be linked with negative effects on occupant health due to possible higher exposure to pollutants [2][3][4] but there is also a need to know how long occupants spend in different rooms to understand their potential levels of exposure to indoor pollutants. This is especially important for studies that model the spread and effect of indoor pollutants rather than measuring them.…”
Section: Introductionmentioning
confidence: 99%
“…The time spent in indoor environments and the high concentrations that can be generated by various domestic activities make indoor exposure particularly influent on the total exposure of individuals. The main recognised sources of PM in confined environments are cigarette smoke, biomass burning for cooking and/or heating purposes and cooking itself, regardless of the used energy source [1], [2]. A study that focused on dwellings with smokers showed respectively 650% and 720% higher PM10 and PM 2.5 concentrations than dwellings without smokers [3].…”
Section: Critical Situations For Indoor Air Qualitymentioning
confidence: 99%
“…Contrarily to the outdoor space, indoor environments, if not adequately built, may contribute to increase the concentrations of air contaminants that comes from outside [9] or that are generated indoors, especially if the ventilation and the rate of exchange of the indoor air are weak. Indeed, similarly to outdoor environments, ventilation acts as the main dispersion mechanism in indoor spaces [10].…”
Section: Introductionmentioning
confidence: 99%